Komparasi Metode Simple Additive Weighting dan Analytical Hierarchy Process dalam Rekomendasi Penyewaan Pakaian - Erlangga Erlangga; Repa Aprilia; Ayu Kartika Puspa; Fenty Ariani (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2021)
Clothing is used as a symbol of the wearer's position. This requires people to follow the lifestyle of clothing trends. Clothing trends today change very quickly and tend to be relatively short-lived. As a result of these changes, people are encouraged to become consumptive. Now people can enjoy it without having to buy expensive clothes. Branded clothes can also be used cheaply. Therefore, clothing rental is a stylish yet fashionable option. There are many clothing rentals shops today, but there is no specific information for renters who are looking for a rental shop that fits their needs. People tend to search and visit rental locations to rent clothes. This rental recommendation makes it easier for tenants to find clothes according to their own criteria. The purpose of this study was to compare the SAW-AHP method which was most suitable for the case of this study. After calculating and comparing the two methods, the SAW method is suitable for this case because it can count all samples, while the AHP method can only count 15 samples according to the Random Index table.